"No brokers to move out of here": A mixed method analysis of the impact of homelessness policy and shelter governance on families residing in NYC shelters. Issue 2 (3rd July 2021) - Beharie, Nisha; Leonard, Noelle R.; Gwadz, Marya
ABSTRACT: Homelessness in the United States (US) has been increasing at an exponential rate over the past three decades, and the US has not experienced the current level of homelessness since the Great Depression of the 1930s. In addition, regulations and policies governing shelters have also increased. Given the historic levels of homelessness and increased bureaucracy, this paper aims to expand on the current literature related to governance of shelters by examining: (1) how families residing in the shelters are impacted by policies related to homelessness and governance within shelters (i.e. shelter rules), and (2) potential points of intervention to improve policy, programming, and shelter governance that better address the growing needs of homeless families. Using a convergent parallel design, we conducted a mixed methods study with caregiver residents and their children (ages 13–17 years), as well as staff, from two family shelters located in a large city in the northeastern US. Findings from the study revealed that policies and programs aimed at assisting homeless families often did not adequately respond to the needs of families (e.g. finding permanent housing), and residents found shelter rules to be overly restrictive. Policy and programming recommendations are provided.